Formation mechanisms of ethyl acetate and organic acids in Kluyveromyces marxianus L1-1 in Chinese acid rice soup - Na Liu; Likang Qin; Laili Hu; Song Miao (Food Science and Human Wellness)
This study aims to explore the formation mechanism of ethyl acetate and organic acids in acid rice soup (rice-acid soup) inoculated with Kluyveromyces marxianus L1-1 through the complementary analysis of transcriptome and proteome. The quantity of K. marxianus L1-1 varied significantly in the fermentation process of rice-acid soup and the first and third days were the two key turning points in the growth phase of K. marxianus L1-1. Importantly, the concentrations of ethyl acetate, ethanol, acetic acid, and L-lactic acid increased from day 1 to day 3. At least 4231 genes and 2937 proteins were identified and 610 differentially expressed proteins were annotated to 30 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways based on the analysis results of transcriptome and proteome. The key genes and proteins including up-regulated alcohol dehydrogenase family, alcohol O-acetyltransferase, acetyl-CoA C-acetyltransferase, acyl-coenzyme A thioester hydrolase, and down-regulated aldehyde dehydrogenase family were involved in glycolysis/gluconeogenesis pathways, starch and sucrose metabolism pathways, amino sugar and nucleotide sugar metabolism pathways, tricarboxylic acid (TCA) cycle, and pyruvate metabolism pathways, thus promoting the formation of ethyl acetate, organic acids, alcohols, and other esters. Our results revealed the formation mechanisms of ethyl acetate and organic acids in rice-acid soup inoculated with K. marxianus L1-1.